2019
DOI: 10.1038/s41467-019-10297-8
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of hexagonal ternary phase Ti2InB2 and its evolution to layered boride TiB

Abstract: M n+1 AX n phases are a large family of compounds that have been limited, so far, to carbides and nitrides. Here we report the prediction of a compound, Ti 2 InB 2 , a stable boron-based ternary phase in the Ti-In-B system, using a computational structure search strategy. This predicted Ti 2 InB 2 compound is successfully synthesized using a solid-state reaction route and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
195
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(211 citation statements)
references
References 42 publications
(47 reference statements)
4
195
0
1
Order By: Relevance
“…Borophane sheets were obtained by exfoliation of a layered MgB 2 superconductor, while to the best of our knowledge there are no experimental reports about the synthesis of 2D MBenes. Recent studies on the partial topochemical deintercalation of Al from layered MoAlB or complete removal of In to produce a layered structure TiB from Ti 2 InB 2 signifies the importance of the judicial choice of suitable precursors for the preparation of novel 2D MBenes.…”
Section: Introductionmentioning
confidence: 80%
“…Borophane sheets were obtained by exfoliation of a layered MgB 2 superconductor, while to the best of our knowledge there are no experimental reports about the synthesis of 2D MBenes. Recent studies on the partial topochemical deintercalation of Al from layered MoAlB or complete removal of In to produce a layered structure TiB from Ti 2 InB 2 signifies the importance of the judicial choice of suitable precursors for the preparation of novel 2D MBenes.…”
Section: Introductionmentioning
confidence: 80%
“…The recent discovery of Ti 2 InB 2 by Wang et al revealed the first laminated hexagonal structure. 11 This hexagonal layered structure is composed of three elements, out of which one is a metal, which do not alone justify it to be classified as a MAX phase or grant an extension of the definition of MAX phases. The composition of hexagonal Ti 2 InB 2 is analogous to general formula (MB) z A y (MB 2 ) x of MAB phases (e.g., orthorhombic Cr 2 AlB 2 and Cr 3 AlB 4 ), which is different from the general M n +1 AX n composition of MAX phases.…”
Section: Discussionmentioning
confidence: 99%
“…All MAB structures display orthorhombic symmetry. The only exception is a recently discovered layered MAB phase, Ti 2 InB 2 , 11 with hexagonal P 6̅ m 2 symmetry (also a hexagonal subgroup of P 6 3 / mmc ). Inspired by this finding and motivated by the previous discovery of i -MAX phases, we here use cluster expansion to theoretically investigate the possibility of chemical ordering in MAB-phase alloys.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] MBenes were predicted to have similarly fascinating properties [21][22][23][24] but have not yet been obtained experimentally, despite several prominent attempts. [24][25][26][27][28] Recent theoretical investigation of the Li-Ni-B system 29 revealed a new Li-rich layered compound Li 2 NiB, whose structure is derived from RT-LiNiB. According to the calculations, only a little extra energy is needed to accommodate an additional Li layer in the structure of the LiNiB parent phase.…”
Section: Introductionmentioning
confidence: 99%